Correlations between performance and shift work in the nursing activities: a pilot approach: Performance and shift work in nursing - Vitale, Elsa; Lupo, Roberto; Fortunato, Silvia; Gualano, Attilio; Giammarinaro, Maria Rita; Bardone, Lorenzo; Mea, Rocco; Calabrò, Antonino; D'Anna, Giuseppe; Della Pietà, Cosimo; Germinni, Francesco (Acta Biomedica Atenei Parmensis, 2022)
Background and Aim of the work. Performance assessment is a key administrative function and an essential component of organizational quality programs, by quantifying it in relation to set goals, standards, expectations and guides to improvement initiatives. The present study aimed to correlate the nursing performance levels perceived by the nurses themselves with the levels of organizational well-being. Methods. An on-line questionnaire was administered to Italian nurses in order to assess nursing performance, thanks to the Six-Dimension on Nursing performance questionnaire and also the wll-being of nursing organization was explored thanks to the Questionnaire on nursing organization- brief form questionnaire (QISO brief form).Results. Significant correlations were assessed between the nursing performance sub dimensions on frequency sub scale and each sub-dimensions of the well-being questionnaire (p